Геоморфологічні екскурсії як засіб пізнання трансформацій рельєфу м. Києва - Денисюк, Л. В; Погорільчук, Н. М. (Київський національний університет імені Тараса Шевченка, 2018)
У даній статті розглядаються особливості геоморфологічних екскурсій як різновиду науково-пізнавальної діяльності, наведено методичні принципи та рекомендації щодо розробки геоморфологічних екскурсій, продемонстровано приклади створених екскурсійних маршрутів, що забезпечують пізнання трансформації рельєфу міста Києва.

The combination of landforms under urban areas of Kyiv plays a decisive role in the formation and development of the city. Various morphosystems of the city has experienced significant transformations over the long-lasting history of Kyiv, which find the reflection in the modern terrain of the city. Geomorphological excursions as a kind of scientific and cognitive activity became one of the ways to explore the relief of the city, learn the interaction of the geomorphological component of the urban landscape and the development of the city at its various historical stages. It’s a promising component of the study program for Earth Science students as long as it’s the best method for studying typical for urban geosystems processes and phenomenons. Excursions ought to fulfill several functions such as scientific propaganda, popularization of geomorphological science, have informative and educational value. According to the main methodological principles, creating a new excursion demands following specific steps, including selection of the goals and purposes of the tour, major and minor destinations due to the topic of the tour, designing tour routes and organizing the final text materials for the tours. There are four geomorphological tours represented in the article. The main purpose of the first excursion is to determine the impact of the landforms features on the construction of Kyiv fortification and to highlight the landscape transformations of the explored areas. The scientific aspect of this route includes exploration of the remnants of the great Kiev retrenchment, the signs of the landslide processes on the right bank slopes of Dnipro river. The second tour is aimed at studying of the transformation of Kyiv ravens - Babyn Yar and Repiiahiv yar , in particular. Due to its purpose of getting students acquainted with the influence of the natural conditions of the area on the course of historical events, the main objects are virgin original landscapes of the ravens as well as transformed areas, the drainage of the stream Babyn Yar and the evidence of an industrial disaster - Kureniv tragedy. The third excursion, highlighted in the article, is aimed at revealing the transformation of the Goloseivsky Forest and provides an overview of the natural and man-made forest landscapes, the influence of the geological and geomorphological conditions of the territory on its economic development, planning and development of the city. The fourth tour aims to provide an insight into the unique natural features and peculiarities of the Kiev hills’ history, as a center of the city formation. The tour is a great way to increase knowledge of the influence of geomorphological conditions on the development of Kyiv at different historical stages, the differentiation of functional parts of the city due to the landforms contrast. Geomorphological excursions demonstrated in the article are the most representative as long as they provide a comprehensive understanding of the relief of the Kiev urban sphere, help to track the development of the city throughout all historical epochs, learn geomorphological factors and their impact on the development of different parts of Kyiv.
Geomorphological excursions as a way of exploration of the Kyiv city landforms transformation
Keywords: геоморфологічні екскурсії; рельєф м. Києва; трансформації рельєфу; geomorphological excursions; relief of Kiev city; landforms transformation